Wheels to sustain: activating the potential of electric vehicles for multiscale grid stability, heat pump penetration, and renewable energy integration - Dik, Abdullah (2024)
Electricity consumption is rising with population growth and technological advancements, particularly in sustainable technologies such as electric vehicles (EVs) and heat pumps (HPs). Environmental policies and advancements in EV technology predict a significant increase in EV adoption, which leads to high electricity demand. Given the environmental impact of fossil fuels, integrating renewable energy sources (RESs) is essential for sustainable electricity generation. However, the intermittent nature of RESs challenges power grid stability, affecting power quality and flow. Emerging evidence suggests that EVs, equipped with Vehicle-to Everything (V2X) technology, can mitigate these issues by acting as distributed energy resources with bidirectional energy flow capabilities, supporting RES integration and grid stability. This research aims to investigate the potential of EVs to enhance energy supply-demand balance and facilitate large-scale RES integration by examining the interaction between EVs, RESs, and energy supply and consumption patterns across various societal scales in the United Kingdom (UK), from individual households to urban areas. To achieve this aim, the research focuses on developing comprehensive stochastic models that address the variabilities and uncertainties in energy demand, supply profiles, and EV charging/discharging operations. It examines how EVs can be utilised for home energy management to enhance RES utilisation. It assesses the impact of EVs with charging management strategies in sustainable residential communities to improve energy management, grid stability and RES integration. Additionally, the study performs an integrated analysis of EVs and intermittent RESs in an urban context to balance energy loads and maximise renewable energy (RE) use. This research employs a range of stochastic analyses, simulations, and analytical techniques to explore the dynamics between EVs, RESs, and energy consumption patterns from individual households to urban areas. The multi-scale approach provides a comprehensive understanding of the interactions and synergies between these elements, addressing the complexities and uncertainties in current and future energy systems. Overall, this research emphasised the potential critical role of EVs in managing energy loads and enhancing RES integration across different societal scales. Despite potential overloading issues when paired with heating demands, EVs also served as advanced storage units. Integrating EVs with sustainable heating solutions, like air-source heat pumps (ASHPs), significantly improved energy management. At the micro-level, EVs equipped with V2X technology effectively managed household energy loads and increased RE usage. At the community level, coordinated actions using smart charging (V1G) and Vehicle-to-Grid (V2G) enhanced energy management and supported substantial RE contributions, stabilising the grid. At the urban scale, strategic EV charging and discharging operations were crucial for addressing energy shortfalls and optimising RE utilisation. Advanced technologies like V2X were essential for balancing energy supply and demand, mitigating peak load issues, and enhancing grid efficiency, which is vital for the UK’s transition to a low-carbon future. The findings provide valuable insights for policymakers and stakeholders, presenting a strategy to maximise the potential of EVs and RESs in developing a sustainable and resilient energy system. However, future energy systems require additional advanced management strategies even with EVs’ potential positive contributions, particularly during cold seasons with higher overloading risks. Stakeholders must consider the specific conclusions drawn at each scale to address these challenges effectively.